The "mystery" of Psathi: some early minoan clay strips and a sealing - Mytilineou, Dimitra; Hallager, Erik (Proceedings of the Danish Institute at Athens, 2000)
During a rescue excavation at the site of Psathi in Crete in 1980, a large amount of unstratified Pre-palatial material was unearthed. The material consisted mainly ofpottery, while it contained also 3,124 small, fat, narrow fragments of clay strips, mostly with string impressions on the surface and often with extra clay applied upon the strings. Such artefacts have to the knowledge of the authors not previously been published from prehistoric sites in the Aegean, and the study of the clay strips, together with practical experiments, leads us to suggest that they may have been used as "buffers" and "stabilizers" when the local poor-quality pottery was fired. In addition to these finds the site produced one of the very rarely found true sealings from the Pre-palatial period in Crete.